EKSISTENSI PROFESI GURU DI TENGAH RENDAHNYA APRESIASI MASYARAKAT - Syah, Pirman; Taslim, Muh.; Hasma; Arifuddin, Kartini Annisa; Sulaiman, Umar; Achruch (Prodi PGMI IAI Sahid, 2026)
This study aims to examine the existence of the teaching profession amidst low public appreciation, using a literature review approach. The main focus of this study is how the teaching profession continues to play a strategic role in the world of education, even though it often does not receive commensurate recognition from society and institutions. Data was collected through searching scientific documents from various online sources such as Tandfonline, Routledge, ERIC, Google Scholar, and educational institution repositories. From the selection results, 14 relevant documents were obtained and analyzed using qualitative analysis techniques model Miles, Huberman, and Saldana, which includes data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, this study refers to the criteria of credibility, transferability, dependability, and confirmability in accordance with the qualitative data analysis guidelines from Moleong. The results of this study indicate that despite the low appreciation of the teaching profession, teachers still have a vital existence in shaping the character and quality of the nation's next generation. However, the social and professional challenges faced require more serious attention from various parties so that the teaching profession receives proper recognition.